'Snap happy' brands: Increasing publicity effectiveness through a snapshot aesthetic when marketing a brand on Instagram. (January 2018) - Colliander, Jonas; Marder, Ben
Abstract: This study examines the effects of a company publishing photos of their products using either (a) snapshot aesthetics, where pictures portray average situations and appear as if though they could have been taken by the average consumer, or (b) traditional studio aesthetics in image based social media. In an experiment where respondents followed an Instagram account of a fashion brand using one of the two aesthetic styles over a period of one week, we demonstrate that in social media, photos with a snapshot aesthetic produce higher brand attitudes and intentions to recommend others to follow the Instagram account. These effects where mediated by higher liking of the images and an increase in source credibility when publishing photos with a snapshot aesthetic. Highlights: A snapshot aesthetic increases brand attitude and word-of mouth intentions on Instagram. A snapshot aesthetic on Instagram proved more effective than a traditional studio aesthetic. Liking the images and source credibility are significant mediators of the favorable brand responses.